Representation of Gender Discrimination and Patriarchal Culture in Movie of Mulan 2020 (Roland Barthes Semiotics Analysis) - Sri Narti; Sapta Sari (LEGAL BRIEF, 2022)
Watching movie is one of the communication activities. The messages that are found to be interpreted by the audience are known as ideologies. Nowadays, the patriarchal ideology in movies often creates criticism in society. This study examines the representation of gender discrimination and patriarchal culture on movie of Mulan 2020 using a qualitative descriptive method. The data analysis technique used the semiotics of Roland Barthes. The results of the research on movie of Mulan 2020 show the condition of Chinese society in the Tang dynasty, dominated by men and there are restrictions on women's movements. There are four forms of representation of gender discrimination. The results found are subordination, marginalization, stereotypes, and violence. Mulan's character is represented as having freedom which refers to existentialism feminism.